Neither a populist nor a vanguardist be! Respecting the wisdom and will of the people. (December 2019) - Taylor, Kenneth A.
In this essay, I consider three different conceptions of 'the people' and what it means to 'respect' their collective will and wisdom: (a) the democratic conception of the people as a sprawling demos, (b) the populist conception of the people as an authentic folk (c) and, finally, the vanguardist conception of the people as the semi-mute masses who stand in need of revolutionary transformation. Although my ultimate aim is to defend the democratic conception of the people over both the populist conception and the vanguardist conception, much of this essay is taken up simply spelling out each of these conceptions of the people and outlining their consequences for the conduct of politics. I begin by contrasting the democratic conception with the populist conception. I then turn briefly to the vanguardist conception. I close with a brief, and admittedly incomplete defence of a particular form of democracy – what I call transformative or ameliorative democracy – which conceives of the people as a self-transformative totality.